Pengelolaan Pelatihan Program Magang Ke Jepang Di PT Keiga Anindha Indonesia - Juliana, Angellia Sheren; Shallahudin, Shallahudin (JURNAL ADMINISTRASI KANTOR; Vol 11 No 2 (2023): Jurnal Administrasi Kantor (Desember 2023), 2023)
This study discusses the management of the apprenticeship program training to Japan in improving the competence of trainees at PT Keiga Anindha Indonesia. The purpose of this research is to obtain data and informants regarding: Planning, implementation, and evaluation in improving the competence of trainees at PT Keiga Anindha Indonesia. Data collection techniques used are interviews, observation, and documentation. The method used in this research is a qualitative approach. The results of this study indicate that the management of the training is prepared by the LPK leadership itself. The training was carried out intensively with the use of dormitories as a mandatory residence for students and training related to aspects of student attitudes/discipline during training activities. Evaluation of training results is carried out regularly, students are satisfied with the training activities provided by PT Keiga Anindha Indonesia because they gain knowledge in the field of Japanese language, work skills, physical and discipline that are useful as provisions for internships in Japan   Keywords : management, training, internship program to Japan.